Analisis Penerapan Sistem Informasi Akuntansi dalam Pengelolaan Data Keuangan pada Bagian Keuangan Dinas Kelautan dan Perikanan Kabupaten Sukabumi - Lestari, Ayu; Noor, Iqbal; Himawan, Irfan Sophan (Economic Reviews Journal, 2024)
This study analyzes the application of accounting information systems in managing financial data at the Sukabumi Regency Marine and Fisheries Service. The phenomenon observed is the lack of efficiency and effectiveness in financial management, as well as challenges in the integration and use of technology by existing human resources. This study aims to identify problems, evaluate the effectiveness of the accounting information system that has been implemented, and provide strategic recommendations to improve the quality of financial management. The research method used is descriptive with a qualitative approach, using data collection techniques through observation, interviews, documentation, and literature study. Data were analyzed using the Miles and Huberman Model involving data reduction, data presentation, and conclusion drawing. The results showed that the Marine and Fisheries Service of Sukabumi District has used two accounting information systems, namely FMIS (2022-2023) and SIPD (2024). Although the new system is equipped with key features that make financial management easier, user satisfaction is still low as SIPD is still in the experimental stage and faces stability issues. Lack of integration with other systems and limited human resources add to inefficiencies. Supervision has not been optimal, indicating the need for a more comprehensive evaluation to improve the implementation of the accounting information system.